Boosting Zinc Electrode Reversibility in Aqueous Electrolytes by Using Low‐Cost Antisolvents - Hao, Junnan; Yuan, Libei; Ye, Chao; Chao, Dongliang; Davey, Kenneth; Guo, Zaiping; Qiao, Shi‐Zhang (Angewandte Chemie International Edition, 2021)
Antisolvent addition has been widely studied in crystallization in the pharmaceutical industries by breaking the solvation balance of the original solution. Here we report a similar antisolvent strategy to boost Zn reversibility via regulation of the electrolyte on a molecular level. By adding for example methanol into ZnSO4 electrolyte, the free water and coordinated water in Zn2+ solvation sheath gradually interact with the antisolvent, which minimizes water activity and weakens Zn2+ solvation. Concomitantly, dendrite‐free Zn deposition occurs via change in the deposition orientation, as evidenced by in situ optical microscopy. Zn reversibility is significantly boosted in antisolvent electrolyte of 50 % methanol by volume (Anti‐M‐50 %) even under harsh environments of −20 °C and 60 °C. Additionally, the suppressed side reactions and dendrite‐free Zn plating/stripping in Anti‐M‐50 % electrolyte significantly enhance performance of Zn/polyaniline coin and pouch cells. We demonstrate this low‐cost strategy can be readily generalized to other solvents, indicating its practical universality. Results will be of immediate interest and benefit to a range of researchers in electrochemistry and energy storage. Water activity and Zn2+ solvation in an ZnSO4 electrolyte are regulated by adding methanol as antisolvent. Methanol gradually interacts with the free and coordinated water in the Zn2+ solvation sheath in the electrolyte, to suppress side reactions and enhance the Zn2+ transference number. Concomitantly, Zn2+ deposition orientation is changed, resulting in dendrite‐free Zn deposition and boosted Zn reversibility.